Does higher health literacy lead to higher trust in public hospitals? - Maja Bertram; Urs Steiner Brandt; Rikke Klitten Hansen; Gert Tinggaard Svendsen (BMC, 2021)
Abstract Background Does higher health literacy lead to higher trust in public hospitals? Existing literature suggests that this is the case since a positive association between the level of health literacy and the level of trust in physicians and the health care system has been shown. This study aims to challenge this assumption. Methods Based on theoretical arguments from game theory and analysis of empirical data, we argue that the association is better described as an inversely u-shaped curve, suggesting that low and high levels of health literacy lead to a lower level of trust than a medium level of health literacy does. The empirical analysis is based on a study of the Danes' relationship to the overall health care system. More than 6000 Danes have been asked about their overall expectations of the health service, their concrete experiences and their attitudes to a number of change initiatives. Results Game theory analysis show that the combined perceived cooperation and benefit effects can explain an inversely u-shaped relationship between social groups and trust in the health care system. Based on quantitative, binary regression analyses of empirical data, the lowest degree of trust is found among patients from the lowest and highest social groups, while the highest degree of trust is found in the middle group. The main driver for this result is that while patients having low health literacy perceive that the health care system is not cooperative, patients with a high level of health literacy have high expectations about the quality, which the health care system might not be able to provide. This reduces the perceived benefit from their encounter with the health care system. Conclusion It is important that health care professionals understand that some patient groups have a higher chance of cooperation (e.g., agreeing on the choice of treatment) or defection (e.g. passing a complaint) than others. In perspective, future research should undertake further qualitative examinations of possible patient types and their demands in relation to different health care sectors, focusing specifically on the opportunities to improve the handling of different patient types.